COMPETITIVENESS AND UNIT LABOUR COSTS IN ROMANIA - NAE TATIANA-ROXANA (Annals of the University of Oradea: Economic Science, 2009)
The present paper presents aspects related on Romanian competitiveness and its determination by unit labour cost (ULC). After reviewing the determinants of national competitiveness, it is taken into consideration the labour market as being an important de